When it rains, it pours: Cyber risk and financial conditions - Thomas M. Eisenbach; Anna Kovner; Michael Junho Lee (Federal Reserve Bank of New York, 2022)
We analyze how systemic cyber risk in the wholesale payments network relates to adverse financial conditions. We show that at the onset of the COVID-19 pandemic, payment activity increased, became more concentrated, and showed intraday liquidity stress. Cyber vulnerability was elevated in late February and early March 2020, with the potential impact of a cyberattack about 40 percent greater than in the remainder of 2020. Policy interventions to stabilize markets mitigated cyber vulnerability, particularly corresponding to large increases in aggregate reserves. We observe that cyber vulnerability and other financial shocks cannot be treated as uncorrelated risks and policy solutions for cyber security need to be calibrated for adverse financial conditions.
Keywords: G12; G21; G28; 330; cyber; banks; networks; payments; COVID-19